Improving Students' Contextual Vocabulary Mastery Through Wordwall.net with Teacher's Guidance - Cahyaningtyas, Lulus Uvi; Laeli, Anita Fatimatul; Fatkurochman, Henri (Journal of Language and Literature Studies, 2026)
The objective of this study is to enhance students’ comprehension of contextual vocabulary in learning procedural texts through the implementation of Wordwall.net in conjunction with teacher guidance. Contextual vocabulary mastery imperative for comprehending procedural texts, as students must be able to interpret action verbs, tools, and sequential instructions that directly impact their academic performance. Preliminary observations suggest that some students encounter challenges in interpreting the meaning of words within the context of tasks, leading to reliance on their peers for clarification.This study employed a quantitative approach with a Classroom Action Research (CAR) design, conducted in two cycles, each comprising planning, action, observation, and reflection. The instrument used was an image-based vocabulary test developed directly by the researcher through the quiz feature on Wordwall.net. results showed improvementin students’ vocabulary mastery and learning independence from the first to the second cycle. .  This finding cotributes to the extant literature by demonstrating that the integration of interactive digital visual media with structured teacher guidance can enhance contextual vocabulary learning in technology-supported classroom. Practically, the integration of Wordwall.net with guided visual vocabulary tasks has been demonstrated to be an effective teaching strategy for the instruction of procedural texts.